Religious orientation and attitudes toward money: relationships with narcissism and the influence of gender - Watson, P. J. (Mental health, religion & culture, 2004)
When combined with Lasch's (1979, 1984) speculations about the narcissism of consumerist society, Sorokin's (1992) analysis of ideational freedom suggests that the Intrinsic Religious Orientation Scale should predict a reduced desire for money and lower narcissism with opposite relationships expected for the Extrinsic Scale. Confirmation of these hypotheses appeared in a sample of 418 undergraduates who responded to the Religious Orientation (Allport and Ross, 1967), Narcissism (Margolis and Thomas, 1980), and Money Attitude (Yamauchi and Templer, 1982) Scales. Also as expected, narcissism was associated with an expanded desire for money. Gender proved to be a noteworthy variable as well, with males, for example, being more narcissistic and less intrinsically religious. Males also expressed higher levels of the especially narcissistic Power-Prestige attitudes about money. These findings most generally indicated that Sorokin's interpretation of freedom might supply useful guidance in future psychology of religion research.